Case Based Learning Teaching Methodology in Undergraduate Health Sciences - Brown, Kaitlyn; Commandant, Mary; Kartolo, Adi; Rowed, Casey; Stanek, Agatha; Sultan, Heebah; Toor, Kabir; Wininger, Victoria (Université d'Ottawa | University of Ottawa, 2012)
Case-based learning (CBL) is an interactive teaching approach involving small-group discussion to determine a range of solutions for a presented patient case. In light of the success that the approach has achieved in numerous professional and undergraduate programs, a pilot project was introduced in 2009 by senior health sciences students, who acted as CBL facilitators, at the University of Ottawa for undergraduate courses in the Interdisciplinary School of Health Sciences (ISHS). In collaboration with faculty professors, the facilitators developed CBL sessions consisting of patient cases that were reflective of the core objectives of health sciences courses. A total of 144 undergraduate students from three ISHS courses took part in these sessions; they were evaluated based on the calibre of their participation and a quiz. The quiz consisted of 5 questions that evaluated the students’ mastery of the concepts covered in the CBL session. The students also completed an evaluation of the pilot project. On a nominal scale of one to five, the students on average scored 4.13 out of a possible 5.00 (SD 1.48) marks on the quiz. In the evaluation, the students rated the project as having an overall learning benefit of 3.82 on a nominal scale of one to four. The evaluation indicates that the students perceived the program as having significant learning value and the quiz marks confirmed that CBL promoted the application of lecture content to practical scenarios. These preliminary findings suggest that implementing CBL in ISHS would enhance students’ academic experience. Further sessions based on this model would improve from more rigorous pre- and post- session assessments.
Keywords: case-based learning; teaching methodology; undergraduate education; pilot projects